Preclinical Study of Single-Dose Moxidectin, a New Oral Treatment for Scabies: Efficacy, Safety, and Pharmacokinetics Compared to Two-Dose Ivermectin in a Porcine Model. - Charlotte Bernigaud; Fang Fang; Katja Fischer; Anne Lespine; Ludwig Serge Aho; Dominique Dreau; Andrew Kelly; Jean-François Sutra; Francis Moreau; Thomas Lilin; Françoise Botterel; Jacques Guillot; et al. (Public Library of Science (PLoS), 2016)
Scabies is one of the commonest dermatological conditions globally; however it is a largely underexplored and truly neglected infectious disease. Foremost, improvement in the management of this public health burden is imperative. Current treatments with topical agents and/or oral ivermectin (IVM) are insufficient and drug resistance is emerging. Moxidectin (MOX), with more advantageous pharmacological profiles may be a promising alternative.Using a porcine scabies model, 12 pigs were randomly assigned to receive orally either MOX (0.3 mg/kg once), IVM (0.2 mg/kg twice) or no treatment. We evaluated treatment efficacies by assessing mite count, clinical lesions, pruritus and ELISA-determined anti-S. scabiei IgG antibodies reductions. Plasma and skin pharmacokinetic profiles were determined. At day 14 post-treatment, all four MOX-treated but only two IVM-treated pigs were mite-free. MOX efficacy was 100% and remained unchanged until study-end (D47), compared to 62% (range 26-100%) for IVM, with one IVM-treated pig remaining infected until D47. Clinical scabies lesions, pruritus and anti-S. scabiei IgG antibodies had completely disappeared in all MOX-treated but only 75% of IVM-treated pigs. MOX persisted ~9 times longer than IVM in plasma and skin, thereby covering the mite's entire life cycle and enabling long-lasting efficacy.Our data demonstrate that oral single-dose MOX was more effective than two consecutive IVM-doses, supporting MOX as potential therapeutic approach for scabies.